Echocardiographic screening of anomalous origin of coronary arteries in athletes with a focus on high take-off - Cantinotti, M.; Giordano, R.; Assanta, N.; Koestenberger, M.; Franchi, E.; Marchese, P.; Clemente, A.; Kutty, S.; D'Ascenzi, F. (healthcare, 2021)
Anomalous aortic origin of coronary arteries (AAOCA) represents a rare congenital heart disease. However, this disease is the second most common cause of sudden cardiac death in apparently healthy athletes. The aim of this systematic review is to analyze the feasibility and the detection rate of AAOCA by echocardiography in children and adults. A literature search was performed within the National Library of Medicine using the following keywords: coronary artery origin anomalies and echocardiography; then, the search was redefined by adding the keywords: athletes, children, and high take-off. Nine echocardiographic studies investigating AAOCA and a total of 33,592 children and adults (age range: 12-49 years) were included in this review. Of these, 6599 were athletes (12-49 years). All studies demonstrated a high feasibility and accuracy of echocardiography for the evaluation of coronary arteries origin as well as their proximal tracts. However, some limitations exist: the incidence of AAOCA varied from 0.09% to 0.39% (up to 0.76%) and was lower than described in computed tomography series (0.3-1.8%). Furthermore, echocardiographic views for the evaluation of AAOCA and the definition of "minor" defects (e.g., high take-off coronary arteries) have not been standardized. An echocardiographic protocol to diagnose the high take-off of coronary arteries is proposed in this article. In conclusion, the screening of AAOCA by echocardiography is feasible and accurate when appropriate examinations are performed; however, specific acoustic windows and definitions of defects other than AAOCA need to be standardized to improve sensitivity and specificity.